Komitmen Kerja Ditinjau Dari Tipe Temperamen dan Jenis Kelamin Survei Pada Karyawan Produksi - M. Wardianto; Syaiful Hadi (Ilmu Psikologi Universitas Yudharta Pasuruan)
The purpose of this study was to determine the significance of variables influence the type of temperament and gender in shaping the work of an employee's commitment. The population in this study were employees of PR. Makmur Jaya Jalan 168 Kepanjen Probolinggo Malang, East Java, which amounts to 2600 + men and women are taken by using a quota sampling technique. Data collection using the scale of work commitments, with Product Moment correlation coefficient between 0.321 to 0.745 and the reliability coefficient of 0.9083532. Meanwhile, to classify the type of temperament using the test tool by Robert J. Temperament Inventory Cruise, Ph.D., and W. Peter Blitchington, Ph.D.  The results showed that the hypothesis which states there is the influence of the type of temperament and gender of an employee's work commitment is rejected at the 5% significance level of 2.21 when the FoA is smaller than F-table 5% at 2.60; Foa at 3.82 smaller than the F-table 5% of 3.84; and FoAB of 0.34 smaller than the F-table 5 2.60% interest. Thus there was no difference in the commitment of employees who work a different type of temperament and gender